2004
DOI: 10.1111/j.1526-4610.2004.04075.x
|View full text |Cite
|
Sign up to set email alerts
|

Simple and Efficient Recognition of Migraine With 3‐Question Headache Screen

Abstract: Positive 3-question headache screen results agreed well with migraine diagnoses based on International Headache Society criteria, clinical impressions, and presence of recurring disabling headaches. These findings support use of the 3-question headache screen to recognize migraine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 15 publications
3
51
1
Order By: Relevance
“…The sensitivity and specificity values are quite similar to those of the German version [3]. Several other validated headache questionnaires exist, most of them constructed as screening instruments for migraine and consisting of 3-8 items based on the IHS criteria [11][12][13][14][15][16][17][18]. Lipton et al presented a very short screening questionnaire for migraine with only three items and were able to achieve a sensitivity of 0.81 and specificity of 0.75, with a kappa of 0.68 [14].…”
Section: Discussionmentioning
confidence: 59%
“…The sensitivity and specificity values are quite similar to those of the German version [3]. Several other validated headache questionnaires exist, most of them constructed as screening instruments for migraine and consisting of 3-8 items based on the IHS criteria [11][12][13][14][15][16][17][18]. Lipton et al presented a very short screening questionnaire for migraine with only three items and were able to achieve a sensitivity of 0.81 and specificity of 0.75, with a kappa of 0.68 [14].…”
Section: Discussionmentioning
confidence: 59%
“…With this purpose and, in accordance to recommendations of experts on management of migraine [7,15,16], instruments for early detection have been developed in recent years, as the Diagnostic Headache Diary [17], the UCSD Migraine Questionnaire [18], the ID Migraine [19], the Brief Headache Screen [20], the 3-Question Headache Screen [21], and other [22-26], with the aim of assisting PC physicians to identify migraine patients in the shortest possible time, due to the important assistance load of health centers. This would not only improve the clinical approach to the diagnosis of migraine, but also contribute to improve patients' awareness of their disease, as often patients are not aware of this disorder and of its social, occupational, and clinical implications [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Despite advances in the understanding of migraine pathophysiology [1,2,3], the creation of short and simple diagnostic questionnaires [4, 5], and the development of triptans for specific acute therapy [6], migraine continues to be inadequately treated. For example, the FRAMIG 2000 study, a population-based survey of migraine diagnosis and treatment patterns in France, found that nearly one fourth of migraineurs had never consulted a physician regarding their migraines, 82% had no medical follow-up for migraine, and 59% of migraineurs who had previously seen a doctor for migraine had lapsed consulting [7].…”
Section: Introductionmentioning
confidence: 99%